Sentença penal absolutória e revisão criminal - Silva, José Edivaldo da (2007)
Exactly not foreseen express in art. 5º (right and basic guarantees) of the Federal Constitution, the Criminal Revision, is inlaid in § 2º of the related device, because decurrent of the regimen and the principles for it adopted, as well as of those deriving ones of the American Convention of Human Rights of 1969 - Pact of San Jose of the Costa Rica - of which Brazil is signatory, thus the revision possesss nature of constitutional action and is only right subjective individual of the convict, destined to rescind definitive conviction, always in benefit of the male defendant. The Law did not establish the hypothesis of the criminal revision pro societate. Thus, considering the principle of relativity and historical of the basic rights, to the light of the proportionality materialized in the technique of the balance of values or valid normative statements when in to crash state, it is considered alteration of the criminal procedural legislation, to make possible the handling of the action of criminal revision pro societate, when the absolution to establish itself in proven documentation false, the example of the case of homicide with the false certificate of death; e when after the sentence, if to discover tests of that was rendered by prevarication, official corruption or corruption of the Judge, since that the criminal types is not to arrive at by the lapsing. Still it considers either granted legitimacy to the Public prosecution service to file a suit asked for revision against acquittal, in the alluded hypotheses and against conviction in the foreseen hypotheses already it has legislation. The method is dogmatic-analytical of the national doctrine and judged legislation and foreign legislation as well as of two of the STF. The dissertation considers, of lege ferenda, the adoption of the criminal revision pro societate, adopting as reference First draft the PL nº 4.506/2001.